Air pollution at human scales in an urban environment. Impact of local environment and vehicles on particle number concentrations. - von Schneidemesser, Erika; Steinmar, Kristina; Weatherhead, Elizabeth C.; Bonn, Boris; Gerwig, Holger; Quedenau, Jörn (Elsevier, 2019)
Air pollution is a global challenge causing millions of premature deaths annually. This is limited not only to developing, but also developed nations, with cities in particular struggling to meet air quality limit values to adequately protect human health. Total exposure to air pollution is often disproportionately affected by the relatively short amount of time spent commuting or in the proximity of traffic. In this exploratory work, we conducted measurements of particle number concentrations using a DiscMini by bicycle. Cycling in residential neighborhoods decreased particulate number concentrations by 17% relative to the ambient average level, and by 22% when cycling through green spaces or parks. Such information is valuable for citizens who may want to reduce their air pollution exposure when moving through a city, but also for policy makers and urban planners who make or influence infrastructure decisions, to be able to reduce exposure and better protect human health, while progress is made to reduce air pollution levels overall.
Keywords: Luftverschmutzung; Partikelmessung; Partikelkonzentration; Stadtverkehr; Fahrradverkehr; Radwegeplanung; Gesundheit